What is Philosophy? What is Knowledge? - Hüseyin Gazi Topdemir (Türk Kütüphaneciliği)
The purpose of this essay is to make an explanatory discussion on philosophy and knowledge in historical context. In addition to an elaboration of the question of what philosophy is the problem of knowledge is also considered. Furthermore, the relationship between philosophy and other disciplines, and social and socie- tal functions are discussed.